A Fresh Perspective on the February Revolution of 1917: a Review of Vladimir Buldakov’s Latest Book - Sadłowski, Michał Patryk (Sensus Historiae, 2025)
The present article offers a review of the book by the Russian historian Vladimir Buldakov entitled Passions of the Revolution: The Emotional Forces of 1917 and published in Russia in 2024 by the New Literary Review. The volume provides an analysis of the principal political, social, and military processes affecting Russia during the February Revolution of 1917. In this context, Buldakov concentrates primarily on the study of the emotions of the Russian population within the revolutionary process. The work is therefore written from the perspective of research into social and crowd psychology. Taking into account Buldakov’s earlier publications, this book may be regarded as a kind of synthesis of his previous studies on the February Revolution of 1917, addressed to a broader readership.